A comparison of US and Scotland youth soccer coaches' legal consciousness regarding concussion safety regulations. Issue 3 (June 2021) - DeMartini, Anne L; Kim, Sungwon; Connaughton, Daniel P; McArdle, David
Due to the severe health consequences of sport related concussion (SRC), governments and sport governing bodies around the world have enacted numerous measures including changes to legislation and rules of the game, and increased emphasis on coach education. This study compared the legal consciousness of girls' youth soccer coaches regarding concussion management under a statutory legal regime in the U.S. and a voluntary regime in Scotland by analyzing qualitative data through ten interviews of girls' youth soccer coaches in Scotland and another ten interviews of girls' high school soccer coaches in the U.S. Utilizing the socio-legal theory of legal consciousness, the findings support the idea that people make connections from their past experiences to shape their understanding of the law, broadly defined. We observed variance between U.S. and Scottish coaches' legal consciousness. Overall, all coaches exhibited a version of conformity to and engagement with SRC management guidance and little resistance. Florida coaches displayed more conformity, likely due to the SRC education mandated by law. Scottish coaches who had coached in the U.S. previously demonstrated the strongest resistance. The findings suggest a need for continued improvement in the implementation of SRC laws and guidelines including updated training and better dissemination of educational materials.